Pattern of Recurrence After Stereotactic Radiotherapy in Prostate Cancer Patients With Nodal Pelvic Relapse. A Multi-Institutional Retrospective Analysis. Issue 1 (January 2022) - Francolini, G.; Bellini, C.; Di Cataldo, V.; Detti, B.; Bruni, A.; Alicino, G.; Triggiani, L.; La Mattina, S.; D'Angelillo, R.M.; Demofonti, C.; Mazzola, R.; Cuccia, F.; et al.
Abstract: Aims: Currently, when nodal pelvic oligorecurrent disease is detected, no standard treatment option is recommended. One possible salvage option is nodal stereotactic body radiotherapy (SBRT). Here we analysed recurrence patterns after nodal SBRT in patients affected by pelvic oligometastatic relapse after radical prostatectomy, and androgen deprivation therapy (ADT)-free survival in this population. Materials and methods: Data on 93 patients consecutively treated in five different institutions for pelvic oligorecurrent disease were reviewed. Inclusion criteria were biochemical recurrence after radical prostatectomy and imaging showing three or fewer metachronous lymphoadenopathies under aortic bifurcation. Patients underwent SBRT on all sites of disease. Concomitant ADT was allowed. Results: After a median follow-up of 20 months (interquartile range 11–41), 57 patients had post-SBRT radiological evidence of relapse, for a median disease-free survival (DFS) of 15 months (95% confidence interval 9–24). Concomitant ADT was administered in 20 patients (21.5%). Overall, eight (8.6%), 21 (22.6%) and 28 (30.1%) patients had prostate bed only, pelvic nodal or distant relapse, respectively. The median ADT-free survival was not reached. Concomitant ADT, International Society for Urologic Pathology pattern at diagnosis < or ≥3, time to relapse ≤ or >12 months, prostate-specific antigen at recurrence < or ≥1.10 ng/ml and prostate-specific membrane antigen staging were not significantly associated with DFS. After relapse, 42 patients (45.2%) received a second SBRT course. Conclusion: Nodal SBRT yielded encouraging DFS and ADT-free survival in this population. Only a minority of patients developed prostate bed recurrence, suggesting that local treatment may be safely avoided. A consistent percentage of patients could be managed with a second SBRT course. Highlights: Patients with pelvic oligorecurrent disease undergoing SBRT. Nodal SBRT yielded encouraging DFS and ADT-free survival in this population. Only a minority of patients developed prostate bed recurrence. Local treatment may be safely avoided. Patients could be managed with a second SBRT course.